(untitled) (Bangladesh Journal of Medical Science, 2024)
Statement of problem. Various studies are present to increase the strength and surface hardness of heat polymerized acrylic resin by addition of material or surface treatments. The present study to evaluate an effect of silica nanoparticles on flexural strength and surface hardness of heat polymerized acrylic resin. Purpose. The purpose of this study was effect of silica nanoparticles, incorporated into Polymethyl Methacrylate, on flexural strength and surface hardness. The present study compared the effect of silanated and non silanated silica nanoparticles on the flexural strength and surface hardness of heat polymerized acrylic resin. Material and Methods. A total of 270 acrylic bars were fabricated, in two batches of 135 each, for testing flexural strength by universal testing machine and surface hardness determined using a digital micro Vickers hardness tester. The control group and subgroups had a sample size of 15 each with varied concentrations of nanoparticles by weight. The fabricated samples were tested for flexural strength and surface hardness. Results. Flexural strength was highest for PMMA (Polymethyl methacrylate) with 0.5% silanated silica nano particles as fillers. In both the groups, the flexural strength decreased with increase in filler concentration. Surface hardness was highest in the PMMA group with non-silanated nano particles as fillers at 5% concentration. In both groups the surface hardness improved with an increase in filler concentration. ANOVA and TUKEY’s HSD test were used. P<0.05 was considered statistically significant. Conclusion. Lower concentrations of surface-treated silica nanoparticles should be used as fillers to enhance the flexural strength of commercially available heat polymerized acrylic resin. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S79-S86